2018
DOI: 10.3389/fendo.2018.00557
|View full text |Cite
|
Sign up to set email alerts
|

An Association of PTPN11 and SHOX Mutations in a Male Presenting With Syndromic Growth Failure

Abstract: In children with genetic syndromes, short stature is frequently a characteristic feature that, when associated with other specific manifestations, significantly aids in clinical diagnosis. In this report, an atypical case of Noonan syndrome (NS) in a 5.5-year-old child with mesomelic short stature is described. Genetic tests revealed two different mutations in this child. As expected in an NS case, a mutation in PTPN11 gene related to the RAS/MAPK signal transduction pathway was identified. Moreover, a mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
1
0
0
Order By: Relevance
“…Ogata et al, in their studies in patients with gonadal dysgenesis in association with data on the growth of people with aneuploidy or polysomy of the sex chromosomes, suggested that tall stature can be caused by an additional copy of the SHOX gene with a shortage of oestrogens. 8 , 16 In our study group, one boy was found to have a short stature and low body weight (case 7), while the others with dupXp22.33 showed a rapid growth rate and intellectual disability, which was also found in patient 3. Three (patients 3, 4 and 6) out of five women with identified duplications of Xp22.31 or Xp22.33 reported delayed speech development and learning difficulties in their childhood.…”
Section: Discussionsupporting
confidence: 51%
“…Ogata et al, in their studies in patients with gonadal dysgenesis in association with data on the growth of people with aneuploidy or polysomy of the sex chromosomes, suggested that tall stature can be caused by an additional copy of the SHOX gene with a shortage of oestrogens. 8 , 16 In our study group, one boy was found to have a short stature and low body weight (case 7), while the others with dupXp22.33 showed a rapid growth rate and intellectual disability, which was also found in patient 3. Three (patients 3, 4 and 6) out of five women with identified duplications of Xp22.31 or Xp22.33 reported delayed speech development and learning difficulties in their childhood.…”
Section: Discussionsupporting
confidence: 51%